Hubungan Motivasi Kader dengan Keaktifan Kader dalam Pelaksanaan Posyandu di Masa Pandemik di Wilayah Kerja UPT Puskesmas Menteng Kota Palangka Raya: Correlation of Motivation with ActivityiIn the Implementation of Integrated Service Posts in Pandemic Time at Menteng Community Health - Agustina, Mia Amelia; Ningsih, Fitriani; Ovany, Riska (Jurnal Surya Medika (JSM), 2023)
The role of cadres is very large in the implementation of Posyandu, some of their responsibilities are monitoring the growth and development of children and toddlers, providing health education to mothers and children, so that people know and are able to practice what needs to be considered in handling children, pregnant women or mothers. If the cadres are not active, the implementation of the posyandu will also be not smooth and as a result the nutritional status of infants or toddlers cannot be clearly detected early. The purpose of this study was to determine the relationship between cadre motivation and cadre activity in the implementation of posyandu. The design of this study used a cross sectional design. The population in this study were all Posyandu Cadres in the Work Area of ​​the Menteng Health Center with a total sample of 55 respondents. The sampling method used is total sampling. The research data was taken using a questionnaire. After tabulating the existing data, it was analyzed using the Chi Square analysis test. The results showed that there was a relationship between cadre motivation and cadre activity in implementing posyandu during the pandemic in the Work Area of ​​the Menteng Health Center UPT, Palangka Raya City (with a P value of 0.000 <a 0.05). Therefore, the Menteng Health Center and the Palangka Raya City Health Office need to increase the role of cadres through cadre training.